2023
DOI: 10.3892/mi.2023.112
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of laboratory characteristics in patients critically ill with COVID‑19 admitted to the intensive care unit (Review)

Stelios Kokkoris,
Angeliki Kanavou,
Panagiotis Kremmydas
et al.

Abstract: In the context of coronavirus disease 2019 (COVID-19), laboratory medicine has played a crucial role in both diagnosis and severity assessment. Although the importance of baseline laboratory findings has been extensively reported, data regarding their evolution over the clinical course are limited. The aim of the present narrative review was to provide the dynamic changes of the routine laboratory variables reported in patients with severe COVID-19 over the course of their critical illness. A search was made o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
2
2
0
Order By: Relevance
“…It should be noted that PLT counts in the patients in the present study were maintained mostly within or higher than the normal range, indicating a hypercoagulation state that persisted over time. This finding is in accordance with that by Wendel Garcia et al ( 24 ), although they are in contrast to findings reported elsewhere showing thrombocytopenia in patients critically ill with COVID-19 ( 27 , 31 ) . The lower counts of PLT in non-survivors relative to survivors may be attributed to their more severe inflammatory status, leading to increased PLT destruction, either mechanically through disseminated intravascular coagulation, or immunologically.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It should be noted that PLT counts in the patients in the present study were maintained mostly within or higher than the normal range, indicating a hypercoagulation state that persisted over time. This finding is in accordance with that by Wendel Garcia et al ( 24 ), although they are in contrast to findings reported elsewhere showing thrombocytopenia in patients critically ill with COVID-19 ( 27 , 31 ) . The lower counts of PLT in non-survivors relative to survivors may be attributed to their more severe inflammatory status, leading to increased PLT destruction, either mechanically through disseminated intravascular coagulation, or immunologically.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that in survivors, although the mean NLR values were gradually decreasing, apart from day 21, they remained elevated, namely >10, indicating, along with the non-resolving lymphopenia, a persistent inflammation. These temporal changes in NLR are consistent with those of previous studies ( 27 , 28 , 35 ), confirming the superior role of NLR, as compared to the WBC count, concerning risk stratification in the clinical context of COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…CK-NAC and CK-MB increases signify serious cardiovascular complications in COVID-19 patients [57]. A total protein decrease is not a common change, though albumin decrease, together with urea, troponin, and PCT increase, are usual changes in the routine laboratory biomarkers for the detection of severe COVID-19 disease [1,56,58,59]. The study of esterase status, with the additional determination of the level of MDA in the blood plasma, revealed statistically significant differences in the following indicators (Table 3): BChE activity with ATCh and BTCh as substrates (decrease by 27% and 37%, respectively) and MDA concentration (increase by 1.5-fold).…”
Section: Resultsmentioning
confidence: 99%
“…The search for diagnostic and prognostic markers, the fastest possible stratification of patients upon admission to hospital, and the assessment of the risk and probability of death in the case of many diseases, including COVID-19, is an urgent task of biochemistry, physiology, and experimental medicine. There are distinct temporal trends in selected routine laboratory parameters between survivors and non-survivors with severe COVID-19 admitted to the intensive care unit (ICU), indicating their importance in the prognosis of clinical outcome [1]. Recent investigations revealed new diagnostic biomarkers of the disease, such as mid-regional pro-adrenomedullin [2,3], monocyte distribution width [4,5], electrolyte imbalances [6], pentameric C-reactive protein [7], and pentraxin-3 [8,9].…”
Section: Introductionmentioning
confidence: 99%